Detection of hydrolytic enzymes produced by Azospirillum brasiliense isolated from root soil (World Journal of Experimental Biosciences, 2014)
Many samples of plant roots soil were collected from Iraq soils, fifty two isolates were obtained from these samples. The ability of Azospirillum brasiliense to produce hydrolytic enzymes such as protease, chitinase, lipase, pectinase and phosphatase was screened. Most isolates produced these hysrolytic enzymes. A. brasiliense (Aw-1) showed the maximum ability to produce these enzymes hydrolyses ratio (5.2 mm) for chitinase, (4.2 mm) for pectinase and complete hydrolyses of protease, pectinase and phosphatase. This isolate was isolated from soil collected from wheat roots.